The expansion of the educational system - Fleming, W. G. (Ontario's educative society ;, 1971)
This volume contains a general introduction to the whole series, followed by seven chapters giving most of the quantitative information in compact form. The introduction discusses some current issues and problems in education: the economic value of education to the individual and to society, the effects of automation, the role of the school in social and emotional development, vocational training and physical development, and the relationship between education and social class. The main body of the text describes the quantitative growth of the educational system and is organized into seven topics: characteristics of the population, school enrollment, the proliferation of educational institutions, university enrolment, enrolment in other post-secondary institutions, and the financing of the system. It contains much specialized statistical material including 46 charts and 225 tables, and will be an excellent work of reference.